(untitled) (Acta Polytechnica CTU Proceedings, 2016)
The paper deals with transportation infrastructure criticality because this quantity determines the State capability to overcome the critical conditions and to ensure the inhabitants survival. The criticality rates for individual types of transportation infrastructure and for the entire transportation infrastructure are determined by data from experts from the areas: transportation; transportation management in the territory; supply chains; public administration; and the Integrated Rescue System. The experts assessed 14 factors, which have been often used in the developed world countries, from the view of human security and development. The result values and their interpretations were determined by using the Multiatribute Utility Theory.